LC-HRMS based method for suspect/non-targeted screening for biomarkers of chemical exposure in human urine. (August 2022) - Tkalec, Žiga; Codling, Garry; Klánová, Jana; Horvat, Milena; Kosjek, Tina
Abstract: Every day we are exposed to a cocktail of anthropogenic compounds many of which are biologically active and capable of inducing negative effects. The simplest way to monitor contaminants in a population is via human biomonitoring (HBM), however conventional targeted approaches require foreknowledge of chemicals of concern, often have compound specific extractions and provide information only for those compounds. This study developed an extraction process for human biomarkers of interest (BoE) in urine that is less compound specific. Combining this with an ultra-high resolution mass spectrometer capable of operating in full scan, and a suspect and non-targeted analysis (SS/NTA) approach, this method provides a more holistic characterization of human exposure. Sample preparation development was based on enzymatically hydrolysed urine spiked with 34 native standards and extracted by solid-phase extraction (SPE). HRMS data was processed by MzMine2 and 80% of standards were identified in the final data matrix using typical NTA data processing procedures. Graphical abstract: Image 1 Highlights: Enzymatic hydrolysis of phase II metabolites is the vital sample preparation step. The method supports high-throughput HBM analysis of urine samples. The method demonstrates low retention time drifts and high mass accuracies. Limits of detection are relevant for HBM exposure studies. 80% of the spiked standards were identified following the non-targeted workflow.